(untitled) (Texas Journal of Medical Science, 2022)
Diagnosis of reactive arthritis is difficult due to absence of a specific test, and deficiency in some minerals may increase the risk that the disease will not quickly resolve. Hence, the aims of current study were to estimate the levels of serum magnesium (Mg), potassium (K) and sodium (Na) in reactive arthritis patients, and evaluate their associations with age and gender. The findings of patient population were revealed an insignificant reduction in Mg with significant decreases in K, and increases in Na. Regarding age, insignificant variation between both age groups, ≤ 30 years and ≥ 31 years, were showed in Mg and Na but not in K that decreased significantly in ≤ 30 years age group when compared to those of ≥ 31 years group. Concerning gender, the findings showed an absence of significant differences between males and females in all elements; Mg, K and Na. In conclusion, this study demonstrated that the serum Mg and K concentrations have an inverse relationship with reactive arthritis, but not for serum Na that having a positive association with the disease. Further research and interventional trials are needed to establish the causal or effect association between serum vitamins / minerals and reactive arthritis since there is real lack of enough information locally and globally.